2008
DOI: 10.3917/mav.019.0114
|View full text |Cite
|
Sign up to set email alerts
|

Proposition d'une typologie des démarches de prospective participative pour les entreprises. Trois cas illustratifs : EDF RαD, AXA France et BASF Agro

Abstract: Résumé Cet exercice de réinterprétation des pratiques de prospective à travers la construction d’une typologie fondée notamment sur la récession des expériences de praticiens et de chercheurs constitue une grille de lecture permettant aux praticiens de concevoir et de conduire des démarches adaptées aux différents besoins des organisations en prenant en compte notamment leurs dimensions cognitives implicites. Il permet d’autre part, de souligner, notamment par les illustrations présentées de la diversité des p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Khiari et al (2011) have demonstrated, through MICMAC, that the definition of new technology for firm's innovation performance requires the reviewing of the analytic framework commonly used to understand entrepreneurial performance phenomenon. Moreover, Bootz and Monti (2008) have used a prospective research to give a prospect for professionals to conceive and manage approaches fitting the organization's needs.…”
Section: Micmac Methodsmentioning
confidence: 99%
“…Khiari et al (2011) have demonstrated, through MICMAC, that the definition of new technology for firm's innovation performance requires the reviewing of the analytic framework commonly used to understand entrepreneurial performance phenomenon. Moreover, Bootz and Monti (2008) have used a prospective research to give a prospect for professionals to conceive and manage approaches fitting the organization's needs.…”
Section: Micmac Methodsmentioning
confidence: 99%
“…If Bootz and Monti (2008) have tried to assess foresight practices with the aim of suggesting a typology which would constitute a means of interpreting allowing the practitioners to conceive and to conduct adapted foresight approach, several authors have focused on the critics directed against strategic foresight practice.…”
Section: Actually It's According To Gaston Berger (1957) a Matter Ofmentioning
confidence: 99%